ANALYSIS OF FACTORS AFFECTING CAPITAL STRUCTURE / LEVERAGE OF WASKITA KARYA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
The purpose of this study was to analyze effects of profitability, Fixed Asset Ratio (FAR), Exchange Rate Risk (ExRisk) and growth on the capital structure / leverage of state-owned enterprises (SOE). This research was conducted at 7 state-owned construction enterprises in Indonesia. The results of this study indicated a positive and significant influence between profitability on the leverage of SOE Karya companies. The existence of a negative and significant influence betw could een Fix Asset Ratio on the leverage of SOE Karya. There was a positive influence between the variables growth and leverage but the statistical value was not significant. Exchange rate risk has a positive but not significant effect on leverage. Keywords: profitability, Fix Asset Ratio, growth, Exchange rate risk . leverage